Insights into the genetic diversity and species distribution of Oswaldocruzia nematodes (Trichostrongylida: Molineidae) in Europe: apparent absence of geographic and population structuring in amphibians - Gulyás, Kristián; Balogová, Monika; Pipová, Natália; Papežík, Petr; Uhrovič, Dalibor; Mikulíček, Peter; Brázová, Tímea; Benovics, Michal (Parasite (Paris, France), 2025)
The genus Oswaldocruzia represents a taxonomically diverse group of nematodes with global distribution. Although Oswaldocruzia species are widespread and exhibit a remarkably wide host range in some species, their genetic diversity and biogeographic patterns remain poorly understood. This study investigated the genetic variability and distribution of Oswaldocruzia spp. in nine anuran species from the genera Bufo, Bufotes, Pelophylax, and Rana across Central Europe and the Balkans. Two species were identified: Oswaldocruzia filiformis and O. ukrainae, each exhibiting a different range of host associations. Phylogenetic analyses based on mitochondrial COI sequences revealed significant haplotype diversity in the generalist O. filiformis, with low geographic and host-associated genetic structuring. In contrast, O. ukrainae, which is closely associated with Bufotes viridis, exhibited only one genetic variant across all samples, highlighting its restricted genetic diversity. The findings emphasize contrasting genetic diversities among nematode parasites exhibiting different levels of host-specificity and expand the known distribution of O. filiformis into new regions of the Balkans. In addition, they highlight the need for additional studies on the ecological and evolutionary factors that influence the genetic diversity of parasites in amphibians.
Keywords: Host Specificity; haplotypy; Anura; Bufonidae; DNA helmintů; Phylogeography; Phylogeny; žáby; fylogeografie; Haplotypes; trichostrongyloidóza; ropuchy; zvířata; Europe; DNA, Helminth; Genetic Diversity; Trichostrongyloidiasis; genetická variace; hostitelská specificita; Genetic Variation; respirační komplex IV; fylogeneze; Amphibian Nematodes; Electron Transport Complex IV; Animals; Oswaldocruzia filiformis; Trichostrongyloidea; Evropa; Host-Parasite Dynamics